2021
DOI: 10.1155/2021/4098270
|View full text |Cite
|
Sign up to set email alerts
|

circ_0075943 Dominates the miR-141-3p/AK2 Network to Support the Development of Breast Carcinoma

Abstract: Background. Breast cancer (BC) progression is related to the disorder of circular RNAs (circRNAs). This study aims to characterize the role of circ_0075943 in BC. Methods. Real-time fluorescent quantitative PCR (real-time PCR) technology was implemented to investigate circ_0075943, AK2 mRNA, and microRNA-141-3p levels. MTT, colony formation method, Transwell, and flow cytometry technique were adopted to investigate cell function. The connection between miR-141-3p and circ_0075943 or AK2 was confirmed by the du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Another study discovered that hsa_circ_0075943 is overexpressed in BC cell lines and tissue specimens [95]. Hsa_circ_0075943 has multiple binding sites for miR-141-3p, which increases AK2 mRNA and protein levels in BC cells and tumor samples [95].…”
Section: Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Another study discovered that hsa_circ_0075943 is overexpressed in BC cell lines and tissue specimens [95]. Hsa_circ_0075943 has multiple binding sites for miR-141-3p, which increases AK2 mRNA and protein levels in BC cells and tumor samples [95].…”
Section: Breast Cancermentioning
confidence: 99%
“…Another study discovered that hsa_circ_0075943 is overexpressed in BC cell lines and tissue specimens [95]. Hsa_circ_0075943 has multiple binding sites for miR-141-3p, which increases AK2 mRNA and protein levels in BC cells and tumor samples [95]. AK2 is an isoform of adenylate kinase, a critical enzyme in the cellular homeostasis of adenine nucleotides, which is involved in malignant transformation by the regulation of metabolism of cancer cells, metabolic signaling, invasion and migration [117].…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in lung adenocarcinoma, AK2 was overexpressed, and high AK2 expression was linked to tumor development and indicated poor prognoses in patients with pulmonary adenocarcinoma 13,14 . It was also reported that AK2 plays a role in hepatocellular carcinoma (HCC), breast cancer, and cervical cancer 15–17 . Although AK2 is related to several malignancies, little is known about the precise underlying mechanisms and its potential cancer‐driving roles, particularly in glioma.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 It was also reported that AK2 plays a role in hepatocellular carcinoma (HCC), breast cancer, and cervical cancer. 15 , 16 , 17 Although AK2 is related to several malignancies, little is known about the precise underlying mechanisms and its potential cancer‐driving roles, particularly in glioma. Thus, it requires more investigation to determine the predictive value and potential roles of AK2 in glioma.…”
Section: Introductionmentioning
confidence: 99%